DIVERSITY OF ANT FAUNA IN 30 KM RADIUS OF KUDANKULAM NUCLEAR POWER PLANT AREA, TAMIL NADU, INDIA - KUMAR, P.; MURUGESAN, A. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A detailed study on the ground dwelling ant diversity was carried around 30 km radius of Kudankulam Nuclear Power Plant area, Tamil Nadu, India during 2011-2012. Pit-fall trap, bait trap and hand-picking methods were used to collect ants from core Zone, buffer Zone I and Buffer zone II and three habitat (sandy area, garden area and plain area), in a sampling sites. A total of 33 species, 18 genera, and 5 subfamilies of ants were recorded. The Formicinae were the most common, with 7 genera and 15 species, followed by the Myrmicinae (6 genera and 10 species), the Ponerinae (4 genera and 5 species) and the Pseudomyrmecinae was represented by only 1 Genera species and 3 species. The six most species rich genera were Camponotus, Paratrechina, Monomorium, Tetraponera, Pheidole and Leptogenys. Higher species abundance is due to the habitat heterogeneity is an important factor to determine the species distribution in the study area. Conservationists should take consider to conserve the ant fauna diversity for there are many direct and indirect contribution on earth.